Examining the women's low labor market participation rate in the Philippines: Is housework the missing link? - Connie Bayudan-Dacuycuy (Philippine Institute for Development Studies (PIDS), 2019)
While the Philippines has achieved several milestones advancing gender equality in the country, there are some areas that can still benefit from further government interventions. One such area pertains to the moderate female participation in the labor market, which hardly improved in the last 26 years. The lackluster participation of women in the labor market presents a continuing concern, and this is amply reflected in Philippine Development Plans and laws designed to support working women. However, other important factors remain to be addressed, and this paper looks into the role of women's housework. The paper also discusses the role of housework on men's market work. Doing so provides a holistic perspective and hence, a better narrative to ensure that both men and women equally benefit from development. Results indicate that housework affects both men and women's participation in market work. However, the study finds a bigger increase in women's market work participation when they do not engage in non-market work and a bigger decrease when their spouses do not share in the household production.
Keywords: 330; housework; market work; labor force participation; gender